2019
DOI: 10.1101/613448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experience-dependent coding of frequency-modulated trajectories by offsets in auditory cortex

Abstract: Frequency modulations are an inherent feature of many behaviorally relevant sounds, including vocalizations and music. Changing trajectories in a sound's frequency often conveys meaningful information, which can be used to differentiate sound categories, as in the case of intonations in tonal languages. However, it is not clear what features of the neural responses in what parts of the auditory cortical pathway might be more important for conveying information about behaviorally relevant frequency modulations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…We also found that some aspects of the surrogacy-induced plasticity that we observed here were most prominent in the late phase of the response to calls. Interestingly, this observation bears similarity to a recent report that secondary auditory cortex (A2) neurons show maternal plasticity in offset responses to frequencymodulated stimuli (Chong et al, 2019). Nevertheless, we are confident that this effect does not bear on our data because our recordings were made in more dorsal thalamo-recipient auditory cortical areas, not in A2.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that some aspects of the surrogacy-induced plasticity that we observed here were most prominent in the late phase of the response to calls. Interestingly, this observation bears similarity to a recent report that secondary auditory cortex (A2) neurons show maternal plasticity in offset responses to frequencymodulated stimuli (Chong et al, 2019). Nevertheless, we are confident that this effect does not bear on our data because our recordings were made in more dorsal thalamo-recipient auditory cortical areas, not in A2.…”
Section: Discussionsupporting
confidence: 90%